The Effect of Problem Based Learning Model with Teaching at the Right Level Approach to Improve Critical Thinking Ability in Physics - Fian Dini; Rosane Medriati; Dedi Hamdani (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
In modern education, teachers act as facilitators who encourage students to learn actively and independently, in line with the demands of 21st century skills such as critical thinking.The study's objectives were to: 1) evaluate how the PBL model with the TaRL approach affected the physics students' critical thinking abilities, 2) ascertain how much the students' critical thinking abilities had improved, and 3) describe how the PBL model with the TaRL approach can improve the critical thinking abilities of physics students. A quasi-experimental design with a non-equivalent control group was used in the study. Two eleventh-grade classes made up the sample: class XI E, which was the control group and used traditional teaching techniques, and class XI D, which was the experimental group and used the PBL model with the TaRL approach. With an average posttest score of 82.68, the experimental group outperformed the control group, which had an average score of 73.26. With a t-test significance value less than 0.001, the results showed a significant difference between the two groups. With an average N-gain score of 0.60 and a Cohen's d value of 1.15, this difference is categorized as substantial with a moderate effect size.